Investigation of chronic diseases in patients with inflammatory bowel disease: a hospital-based case-control study - Ali Zabihi; Mehrdad Kashifard; Seyedeh Roghieh Jafarian Amiri; Mahdi Sepidarkish; Valiollah Padehban; Mojtaba Qanbari Qalehsari (Babol University of Medical Sciences, 2022)
Background: Inflammatory bowel disease (IBD) is a broad term that refers to a group of chronic inflammatory disorders that have an unknown origin and might be associated with other diseases. The aim of this study was to determine the frequency of chronic diseases in patients with IBD. Methods: In this case-control study, 280 patients with IBD were compared with 280 healthy individuals, frequency-matched by age, sex, place of residence and marital status. Random sampling was performed in patients that referred to the internal medicine and gastroenterology wards of hospitals affiliated to Babol University of Medical Sciences. Data collection tools included a demographic questionnaire and a checklist for chronic diseases, which were completed through interviews with the case and control groups. Results: Two hundred and twenty-nine (81.78%) patients with IBD had at least one chronic disease. Patients with IBD were at increased risks of rheumatoid arthritis (OR= 4.48, 95%CI: 1.48, 13.54, P= 0.008), eye diseases (OR= 3.49, 95%CI: 1.68, 7.28, P= 0.001), liver diseases (OR= 2.74, 95%CI: 1.40, 5.34, P= 0.003 ), anemia (OR = 2.53, 95%CI: 1.56, 4.13, P= 0.000), depression (OR= 2.43, 95%CI: 1.58, 3.74, P= 0.000), skin diseases (OR= 2.36, 95%CI: 1.18, 4.74, P= 0.015) and hypertension (OR= 1.77, 95%CI: 1.06, 2.95, P= 0.028). Conclusion:  The frequency of chronic diseases associated with IBD has been high, therefore, physicians and health care professionals should consider the possibility of other chronic diseases when dealing with IBD patients.